Pengaduan Penyintas Pelecehan Seksual di Kota Makassar Perspektif Hifzul ‘Irḍi: The Role of Hifzul 'Irḍi in Protecting Sexual Harassment Survivors' Complaints in Makassar City - Has, Nisaul Haq Bintu; Mustawakkal, Mustawakkal; Sabir, Muhammad (Universitas Islam Negeri Alauddin Makassar, 2025)
This research aimed to analyze the realities of sexual harassment survivors in Makassar City, its impact on their lives, and examine the concept of Hifzul ‘Irḍi within the maqāṣid al-syaria as a framework for protecting survivors' honor. This research approach was qualitative, with data collected through in-depth interviews with survivors, legal counselors, and complaint service providers, as well as a review of relevant documents and literature as secondary data. The data was analyzed thematically to identify patterns in survivors' experiences and their relevance to the principles of protection in Islamic law. The results showed that survivors were often reluctant to report due to confusion in determining legal action, concerns about the perpetrator's position of power, and psychological burdens such as anxiety, stress, and deep trauma. Victims also faced a moral dilemma between maintaining the institution's reputation and pursuing justice. Sexual harassment had a significant impact on survivors' lives, not only causing deep emotional wounds but also creating social stigma, discrimination, and isolation that damage their interpersonal relationships. Hifzul ‘Irḍi's analysis emphasized that maintaining honor was an essential right that must be upheld, while the existence of complaint services was a crucial instrument in restoring the dignity of survivors and preventing similar cases in the future. This research recommends strengthening human rights-based policies and the maqāṣid al-syaria to create a safe, responsive, and victim-friendly social ecosystem.